Myocarditis in Adults Over 65 Years of Age Due to Complications of Covid-19: Clinical Features and Drug Treatment Strategies - o’g’li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2023)
Myocarditis associated with novel coronavirus infection (COVID-19) is a difficult diagnosis from all points of view. The clinical manifestations of this pathology may be nonspecific or erased, while its long-term consequences for the patient are unknown. Diagnostic approaches are complex and practically impossible in covid clinics. Therapy carried out in patients with COVID-19 carries a potential threat to the myocardium. The aim of this review was to summarize the information available to date on the clinical aspects and medical treatment of inflammatory myocardial injury in COVID-19. More than 300 relevant literature sources have been analyzed, and the most significant information in the light of the problem under discussion is given in the article. The results of the analysis of the current world literature have shown convincing evidence of the possible development of myocarditis as part of a new coronavirus infection. Histological verification of myocardial damage associated with COVID-19 presents significant difficulties, since endomyocardial biopsy is not always possible in conditions of severe infection. In this regard, the statistics do not reflect complete information on the prevalence of myocarditis associated with COVID-19. Due to insufficient knowledge of the pathogenesis of inflammatory myocardial damage, drug approaches have not been developed and are mainly empirical in nature. Due to the ambiguity of the prognosis of patients with myocarditis associated with COVID-19, further study of the problem is required.